New contributions on Medical Humanities - Wahren, Carlos (Revista del Hospital Italiano de Buenos Aires, 2024)
Miguel de Asúa, Doctor of Medicine and History, was summoned by various medical societies and institutions to enrich their congresses, seminars and publications. From there emerged the works that compose De Hipócrates a Clío, where he rigorously approaches topics such as the relationship between philosophy and medicine, the consequences of epidemics or death in infancy.
Keywords: History of medicine; epidemics; pediatrics; medical humanism